Growth and Yield of Purple Kculli Corn Plants under Different Fertilization Schemes - Teresa Romero-Cortes; Lis Tamayo-Rivera; Mario A. Morales-Ovando; José E. Aparicio Burgos; Victor H. Pérez España; Martin Peralta-Gil; Jaime A. Cuervo-Parra (Journal of Fungi, 2022)
Globally, corn is the most economically important crop, surpassing other cereals of economic importance. However, the tillage methods, monoculture and the abuse of synthetic agrochemicals used in Mexico have led to the loss of fertility and soil yield. In this sense, the application of alternative fertilization methods based on chemical fertilizer, organic matter and biofertilizer, applied alone or in combination, can stimulate the defense systems of corn plants and increase their yield. Therefore, in this research, some fertilization schemes were tested on purple corn plants of the Kculli race through the evaluation of some growth and yield variables, as well as the subsequent evaluation of the chemical characteristics of the corn grain produced in each fertilization scheme. The results indicate highly significant differences (p ≤ 0.05) between treatments, for the different growth and yield variables studied. Of all the fertilization schemes evaluated, treatment T7 obtained the best grain yield of 6.19 ± 0.07 t ha−1, with respect to treatment T1 of 1.02 ± 0.01 t ha−1, as well as the highest protein content and starch quality. Being clear the positive effect of the adequate contribution of the macro and micronutrients used exerts on the corn crop in each of the fertilization schemes studied. On the other hand, the analysis carried out on the grains was found within the values reported by other authors.